Ciało, intymność, wieczność. Śladami Józefa Tischnera - Kaczmarek, Agnnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
The main problem of this article is Jozef Tischner’s thought about the disease, death and mercy. The experience of the disease, which are also experienced Tischner– makes the area of intimacy, so very personal and even closed can be reduced. So arranged the body enters a new area of dialogue – values and meetings, which in the longillness and death radically change their character. Disease and related existential experiencemade a special return in thought Tischner directing them to the mercy of the problemand resuming the problem of death situated in the context of eternity.